1985
DOI: 10.2466/pms.1985.61.1.196
|View full text |Cite
|
Sign up to set email alerts
|

Interposition and Size Constancy: A Developmental Study

Abstract: 27 children (mean age 6.7 yr.) and 84 adults (mean age 26.3 yr.) were asked to judge the sizes of human figures in photographs. Half the cards contained interpositional depth cues while the other half did not. Both groups of subjects showed better size constancy with interposition present than without it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Mandes (1985) presented children and adults with images of human figures and asked the participants to judge the size of each figure. Half of the images contained interposition, and half did not.…”
Section: Interactionsmentioning
confidence: 99%
“…Mandes (1985) presented children and adults with images of human figures and asked the participants to judge the size of each figure. Half of the images contained interposition, and half did not.…”
Section: Interactionsmentioning
confidence: 99%
“…Early artists 88 GORDON AND ROSENBLUM established that observers are able to detect depth and relative object positions from the interposition of visible surfaces (e.g., Mandes, 1985;Olson, 1975). Research on stationary occlusion (i.e., involving stationary surfaces and observers) has shown that the interposition of surfaces can induce perception of depth and surface separation (Cutting & Vishton, 1995;Mandes, 1985).…”
mentioning
confidence: 99%